Analysis of State Capital Participation - Diky Paramitha; Novita Nugraheni; Izzia An-Nabila (International Journal of Business and Applied Economics, 2023)
The purpose of this research was carried out are to know how the utilization of permanent long-term government investment, in the form of State Equity Participation (PMN) in SOEs, is realized. The implementation of government investment in accordance with Government Regulation of the Republic of Indonesia number 63 of 2019 which is then associated with BUMN that obtain PMN. The research was conducted using quantitative Descriptive methods with the acquisition of analysis results and conclusions based on a review of data and information that has been published. The results of the study focused on investment in the form of PMN directly and indirectly and its benefits for the state budget.